Regulation of a Chemical Defense against Herbivory Produced by Symbiotic Fungi in Grass Plants - Zhang, Dong-Xiu (American Society of Plant Biologists, 2009)
Neotyphodium uncinatum and Neotyphodium siegelii are fungal symbionts (endophytes) of meadow fescue (MF; Lolium pratense), which they protect from insects by producing loline alkaloids. High levels of lolines are produced following insect damage or mock herbivory (clipping). Although loline alkaloid levels were greatly elevated in regrowth after clipping, loline-alkaloid biosynthesis (LOL) gene expression in regrowth and basal tissues was similar to unclipped controls. The dramatic increase of lolines in regrowth reflected the much higher concentrations in young (center) versus older (outer) leaf blades, so LOL gene expression was compared in these tissues. In MF-N. siegelii, LOL gene expression was similar in younger and older leaf blades, whereas expression of N. uncinatum LOL genes and some associated biosynthesis genes was higher in younger than older leaf blades. Because lolines are derived from amino acids that are mobilized to new growth, we tested the amino acid levels in center and outer leaf blades. Younger leaf blades of aposymbiotic plants (no endophyte present) had significantly higher levels of asparagine and sometimes glutamine compared to older leaf blades. The amino acid levels were much lower in MF-N. siegelii and MF-N. uncinatum compared to aposymbiotic plants and MF with Epichloë festucae (a closely related symbiont), which lacked lolines. We conclude that loline alkaloid production in young tissue depleted these amino acid pools and was apparently regulated by availability of the amino acid substrates. As a result, lolines maximally protect young host tissues in a fashion similar to endogenous plant metabolites that conform to optimal defense theory.